2021
DOI: 10.3389/fpsyg.2021.555446
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Physiological and Performance-Based Metrics to Estimate Pilots' Cognitive Workload

Abstract: This paper discusses the utilization of pilots' physiological indications such as electroencephalographic (EEG) signals, ocular parameters, and pilot performance-based quantitative metrics to estimate cognitive workload. The study aims to derive a non-invasive technique to estimate pilot's cognitive workload and study their correlation with standard physiological parameters. Initially, we conducted a set of user trials using well-established psychometric tests for evaluating the effectiveness of pupil and gaze… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Our findings regarding longitudinal stick data are in line with previous findings from low-fidelity simulator studies [12], [21], in which increased task difficulty (i.e., flying within the virtual boundaries of a given flight path of decreasing sizes, and adding secondary tasks to the initial flight maneuvers) increased Duty Cycle and Aggressiveness. As Gray [22] explains, when pilots are flying, they do not constantly change their control inputs.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our findings regarding longitudinal stick data are in line with previous findings from low-fidelity simulator studies [12], [21], in which increased task difficulty (i.e., flying within the virtual boundaries of a given flight path of decreasing sizes, and adding secondary tasks to the initial flight maneuvers) increased Duty Cycle and Aggressiveness. As Gray [22] explains, when pilots are flying, they do not constantly change their control inputs.…”
Section: Discussionsupporting
confidence: 91%
“…In simulated flights, increase in workload has been associated with increased deviations from targeted flight parameters [11], [12]. Behavioral measures that target workload are of importance in the understanding of learning [13], and adaptive human-controlled systems [14].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst three studies using subjective measures of assessment reported no difference in cognitive load between LS and RALS, 35 , 37 , 40 these findings are likely limited by the insensitivity of the methods employed. 50 Collectively, data suggest that cognitive demand is greater in LS.…”
Section: Discussionmentioning
confidence: 99%
“…Further research is required to quantify cognitive fatigue in surgeons using objective measures such as EEG, which are less prone to the limitations of subjective assessment. 50 , 53 , 54 This will provide a direct objective measurement of brain function, unlike indirect objective measurements based on heart rate or skin conductance. If changes in fatigue during surgery can be determined objectively, then the relationship to musculoskeletal fatigue should be investigated in tandem to determine if cognitive fatigue is causative of musculoskeletal fatigue, caused by a reduction in central drive.…”
Section: Discussionmentioning
confidence: 99%